Distribusi Indeks Massa Tubuh (BMI) dan Intensitas Nyeri Punggung Pada Ibu Hamil Trimester Ketiga: Distribution of Body Mass Index (BMI) and Back Pain Intensity in Third Trimester Pregnant Women - Nella Vallen Ika Puspita; Desi Soraya; Qomariyah (Indonesian Journal of Midwifery (IJM), 2026)
The appearance of discomfort in the back area is often triggered by biomechanical and physiological transformations that occur during the third trimester of pregnancy. Nutritional conditions represented through Body Mass Index (BMI) figures are strongly suspected to be the variables that trigger the emergence of these disorders in pregnant women. Departing from this, this study was carried out to map the distribution of BMI categories as well as the degree of back discomfort felt by pregnant women in the third trimester phase within the scope of the Gunungpati Health Center, Semarang. Through a quantitative-descriptive methodology, this research involved 31 subjects taken using a saturated sample procedure (total sampling) from a population of pregnant women with similar pain complaints. The determination of BMI status was carried out objectively through anthropometric calculations (height and weight), while to evaluate the level of pain, the researcher applied the Numerical Rating Scale (NRS) instrument. Data analysis was carried out univariate and presented in the form of frequency and percentage distributions. The results showed that most of the respondents had a normal BMI as many as 21 respondents (67.7%), while the overweight category as many as 10 respondents (32.3%). The intensity of back pain was dominated by the moderate category of 23 respondents (74.2%), followed by severe pain as many as 5 respondents (16.1%) and mild pain as many as 3 respondents (9.7%). The conclusion of the study showed that the majority of pregnant women in the third trimester had normal BMI with moderate back pain intensity. Promotive and preventive efforts are needed through nutritional status monitoring and health education to reduce back pain complaints in pregnant women.   Abstrak Munculnya rasa tidak nyaman pada area punggung sering kali di picu oleh transformasi biomekanik serta fisiologis yang terjadi selama masa kehamilan trimester III. Kondisi nutrisi yang direpresentasikan melalui angka Indeks Massa Tubuh (IMT) diduga kuat menjadi variabel yang memicu munculnya gangguan tersebut pada wanita hamil. Berangkat dari hal tersebut, studi ini dilaksanakan guna memetakan sebaran kategori IMT sekaligus derajat ketidaknyamanan punggung yang dirasakan oleh ibu hamil di fase trimester ketiga di lingkup Puskesmas Gunungpati, Semarang. Melalui metodologi kuantitatif-deskriptif, riset ini melibatkan 31 subjek yang diambil menggunakan prosedur sampel jenuh (total sampling) dari populasi ibu hamil dengan keluhan nyeri serupa. Penentuan status IMT dilakukan secara objektif melalui kalkulasi antropometri (tinggi serta berat badan), sementara untuk mengevaluasi level rasa nyeri, peneliti mengaplikasikan instrumen Numerical Rating Scale (NRS). Analisis data dilakukan secara univariat dan disajikan dalam bentuk distribusi frekuensi dan persentase. Hasil penelitian menunjukkan sebagian besar responden memiliki IMT kategori normal sebanyak 21 responden (67,7%), sedangkan kategori overweight sebanyak 10 responden (32,3%). Intensitas nyeri punggung didominasi kategori sedang sebanyak 23 responden (74,2%), diikuti nyeri berat sebanyak 5 responden (16,1%) dan nyeri ringan sebanyak 3 responden (9,7%). Simpulan penelitian menunjukkan bahwa mayoritas ibu hamil trimester III memiliki IMT normal dengan intensitas nyeri punggung kategori sedang. Diperlukan upaya promotif dan preventif melalui pemantauan status gizi dan edukasi kesehatan untuk mengurangi keluhan nyeri punggung pada ibu hamil.